PENINGKATAN KUALITAS DAN PERAN ASET DESA UNTUK BIDANG KESEHATAN DALAM RANGKA PENCEGAHAN STUNTING PADA REMAJA - Anas Ma'ruf Annizar; Rena Andria Rahma (As-Sidanah, 2023)
Kencong Village is one of the Kencong District villages in Jember Regency, East Java Province. Stunting is a matter that is the main program of the Health Service. However, if you look at it, the stunting rate in Kencong Village has not yet touched zero, even though there are many Community Health Centers (PusTu), Healthy Village Homes (RDS), and Elderly and Children’s Posyandu. The goals and hopes of the KKN Team are that Health Service Assets can improve and develop their quality and role in preventing stunting rates, especially in adolescents. This program is based on the KKN research method, namely the ABCD (Asset-based Community Development)-based KKN application method. The results showed that this socialization was adequate, which can be seen that the posttest average score of 69.53 was more greater than the average pretest score of 58.60, so it could be concluded that there was an increase in the score of 10.93%. The result also showed that this program deserves to be continued consistently and more optimally by collaborating between assets health service with other assets such as village officials or social communities.